Relationship between mental skill and sport injuries in soccer players of Tehrans team in premier league - Karim Biglar; Mohammad Hossein Alizadeh; Mohammad Khabiri (Sport Sciences and Health Research)
Introduction: Numerous empirical studies suggest that specific psychological factors influence the frequency and severity of sport injuries. Method: The aim of present study was to examine the relationship between fundamental psychological skills, psycho-somatic skills, cognitive skills and incidence of injuries in football players of Tehran premier league. 108 players from four teams of Iran premier league participated in the study. Research data was collected by injury report form and Ottawa mental skills assessment tool-3. Pearson correlation test at significant level of 95% were used for analyzing the data. Result: Results indicated that 89.5% of players experienced at least one injury during one season which 90.7 % of them resulted in 1-3 days missing of match or training. The findings also indicated that in football players of premier league there is inverse and significant relationship between psychological skills (p=0/0001) and its subdivisions including fundamental psychological skills (p=0/006), psycho-somatic skills (p=0/0001), cognitive skills (p=0/0001) and incidence of sport injuries. Conclusion: The findings of present study show that having high levels of psychological skills helps premier league players to handle stressful situations in sports through enhancing self-confidence and other psychological factors confronting harmful psychological factors such as stress and anxiety and lead to decrease in injury incidence. Thus officials, coaches, physicians and sport psychologists are recommended to educate essential psychological skills.